Compatibilidade e associação do óleo de mamona a Beauveria bassiana no controle de Bemisia tabaci biótipo B e seletividade a Trichogramma pretiosum - Marques, Míriam de Almeida (2015)
Vegetable oils and the fungus Beauveria bassiana has been tested on Bemisia tabaci, resulting in median controls of nymphs at field level. Several studies have shown that the efficiency of B. bassiana for control of Bemisia tabaci nymphs can be increased by combination with other control agents. Thus, this study was conducted to evaluate: the effect of the combination of B. bassiana with sublethal doses of castor oil in the mortality of B. tabaci nymphs; the compatibility of castor oil with B. bassiana and Trichogramma pretiosum, parasitoid of caterpillar eggs most used in the world. The effect of the castor oil at 100% (v/v) on conidia germination, vegetative growth and sporulation of B. bassiana after 24 h and seven, 15, 60, 90, 120 days of storage at 4°C and 26°C was evaluated in two experiments at laboratory. The effect of castor oil (Rícino®) at 1%, 2%, 3%, 4%, 5% and 6% (v/v) and neutral detergent at 2% (v/v) (emulsifier for the oil) on immature stages of T. pretiosum (egg, larva, pre-pupae and pupae) of parasitoid was also tested at laboratory. the chlorpyrifos insecticide 0.5 L a.i./ha and distilled water In the first stage of the study several experiments were conducted at screenhouse to determine the sublethal dose of commercial castor oil Azevedo® and Rícino® at 0.25%, 0.5%, 1.0%, 1.5 %, 2.0%, 3.0%, 4.0%, 5.0% and 6.0% (v/v) on mortality of different instars of B. tabaci. The castor oil was emulsified with Silwet® L-77 (0.01%, v/v), Zupp® neutral detergent (1%, 2%, 3% and 4%, v/v) and Solub'oil® (0.005%, 0.015%, 0.045%, 0.09%, 0.20% and 0.27%, v/v). The insecticide thiamethoxam 250 WG, was included as the chemical standard tested at label rate recommended by the manufacturer of 0.17 g a.i./L. Distilled water was used as the untreated control. In the second stage, B. bassiana CG1229 at 1×106 and 1x107 conidia/mL was tested alone or in combination with castor oil at 1% (v/v) emulsified in Silwet® L-77 0.01% (v/v) or Solub'oil® at 0.05% and 0.1% (v/v) on second instar nymphs of B. tabaci at screenhouse. Mortality of first instar to the fourth nymphs increased with an increase in concentration of castor oil and emulsifiers. Nymphs of the first and second instar were more susceptible to castor oil and 0.01% Silwet (v/v) than the third and fourth instars.The neutral detergent at 1%, 2%, 3% and 4% (v/v) killed 28.6%, 52.7%, 64.4% and 69.3% of second instar nymphs, respectively. When neutral detergent at 2% (v/v) was combined with castor oil 1% (v/v), killed 88.03% and 79.34% nymphs of first-second and third-fourth instar, respectively. The Solub'oil at 0.005%, 0.015%, 0.045%, 0.09% and 0.27% (v/v) killed 34.9%, 26.1%, 30.9%, 38.1% and 70.1% of second instar nymphs, respectively. When the Solub'oil at 0.2% (v/v) was combined with castor oil Azevedo at 1% (v/v), mortality of second instar nymphs was 84.71%. Reductions in the vegetative growth of B. bassiana by castor oil and Solub'oil were observed after 120 days of storage at 26°C when compared to pure conidia of the fungus. Conidia viability and conidiogenesis of B. bassiana was not affected by Castor oil at 26 ° C in all dates. Mortality of B. tabaci nymphs was significantly lower when castor oil + Silwet® L-77 was combined with B. bassiana (16.93%) compared to the fungus alone (57.94%). It was observed that Silwet® L- 77 at 0.01% did not emulsify efficiently the castor oil, not allowing conidia to germinate (9.82%). The combination of conidia of B. bassiana + castor oil + solub'oil and B. bassiana + Solub'oil significantly increased mortality of nymphs of B. tabaci (91.66% and 85.46%, respectively) compared to B. bassiana, castor oil or Solub'oil tested alone (75.57%, 59.12% and 53.92%, respectively). The Solub'oil at 0.5% or 1.0% did not affect the germination of conidia of B. bassiana (96.5%). Egg-larval stage of development of T. pretiosum was the least affected by different concentrations of castor oil + neutral detergent at 2% (v/v), with 81.9% of adult emergence of than the stages of pre-pupae and pupae, with 24.88% and 18.30% of emergency, respectively. Castor oil at 1% and 2% (v/v) was selective and innocuous to the egg-larval stage. All oil concentrations were considered mildly or moderately harmful to prepupae and pupae stages of T.pretiosum and caused significant reductions in adults emergency of parasitoid. The neutral detergent at 2% (v/v) did not affect immature stages of T. pretiosum, with emergency of adults ≤ 95.8% and it was classified as harmless to this parasitoid. Castor oil and emulsifiers have the potential to control B. tabaci biotype B. Castor oil when combined with conidia of B. bassiana + Solub'oil or only with Solub'oil increases mortality of nymphs of B. tabaci. Castor oil is selective to all T. pretiosum stages of development at concentrations ≤ 2%.